Comparison of LIBS results on ITER-relevant samples obtained by nanosecond and picosecond lasers. (January 2019) - Paris, P.; Butikova, J.; Laan, M.; Hakola, A.; Jõgi, I.; Likonen, J.; Grigore, E.; Ruset, C.
Highlights: Ps laser resulted in same Hα LIBS signal as ns laser at two times lower laser fluence. Accuracy of Dα curve fitting was determined by overlap with more intensive Hα line. Relative Standard Error of the fitting of Dα profile was two times lower for ps laser. Intensities of W lines were less influenced by self-absorption with ps laser. Abstract: ITER foresees applying laser induced breakdown spectroscopy (LIBS) as a tool for quantitative assessment of fuel retention in the first walls. One open problem related to LIBS application is the choice of the laser type. Here we compare two Nd/YAG lasers with different pulse durations, 0.15 and 8 ns, working at λ = 1064 nm for LIBS studies of samples with D -doped W/Al coatings of ≈ 3 μm thickness (Al is used as a proxy of Be) on Mo. Low pressure argon was used as a background gas. Experiments were done in conditions where other factors (broadening of spectral lines, signal-to-noise ratio, limited thickness of coatings etc.) did not shadow the effect of laser pulse duration. For these reasons, low pressure argon was used as the background gas and fluences were kept at comparatively low values. Spectra of laser-produced plasma were recorded as a function of the number of laser pulses. Partially overlapping lines of hydrogen isotopes were fitted with Voigt contours, intensities were fitted and depth profiles of deuterium were reconstructed. The relative standard error of curve-fitting of spectra recorded with the laser of shorter pulse duration was two times smaller than that recorded by the longer pulse laser. The electron density was found from the Stark broadening of Hα line of the laser-produced plasma and the electron temperature of plasma was found on the basis W and Mo lines. It was found that in the case of ps laser an acceptable accuracy of the detection of deuterium was possible at considerably lower values of fluence. Steps needed for comparison of ps and ns lasers in ITER-relevant conditions were discussed.